Leadership and Organizational Commitment in Improving Employee Performance: The Role of Job Satisfaction as a Mediator - Fardiansyah, Ibnu Eka; Jumady, Edy; Djaharuddin, Dharmawati (Manunggal Halim Jaya, 2025)
This study explores the interconnected roles of leadership, organizational commitment, and job satisfaction in enhancing employee performance, with job satisfaction as a mediating variable. Utilizing a qualitative approach grounded in literature review, the study synthesizes insights from existing research on transformational and transactional leadership, various dimensions of organizational commitment, and the impact of job satisfaction on employee productivity. Thematic analysis reveals that transformational leadership, characterized by inspiration and motivation, significantly enhances job satisfaction and organizational commitment, positively influencing employee performance. Conversely, transactional leadership, which emphasizes rewards and structure, has a more limited impact on long-term commitment and satisfaction. Job satisfaction is identified as a critical mediator, enabling leadership and commitment to translate into increased performance outcomes. This study contributes theoretically by validating job satisfaction's mediating role in workplace dynamics and highlighting affective commitment as a key factor for sustained performance. Managerial implications underscore the importance of transformational leadership training and strategies to boost job satisfaction, such as recognition programs and professional development. Future research should consider cross-cultural, longitudinal, and industry-specific analyses to deepen understanding of these constructs in varied organizational contexts.